An investigation into linking the semantic and syntactic representations in simple sentences (english vs vietnamese) - Trần Thị Dưỡng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study attempted to describe the various components of a description of grammatical structure as well as the principles that links syntactic and semantic representations in simple sentences together, based on the explanatory framework of RRG. In addition, the study was designed to yield an explicit analysis and an application of this theory in English and Vietnamese from which the similarities and differences were drawn. Furthermore, the study also had a part in discovering the interaction among structure, meaning, and communicative function in English and Vietnamese. Some conclusions and implications to the teaching and learning English concerning the syntactic structure of sentences and facets of the meaning of linguistic expressions have been put forward to help learners to perfect their communicative ends.